Odenigbo - Chigbo, Thomas (Evans Brothers (Nigeria Publishers) Ltd, 1976)
The day dawned a little too early for it had failed to put on its usual early morning bright smiles. It may have been because Odenigbo had slept badly and it did not seem long after he had gone to bed that his usual early morning sentry, the giant cock which normally shared a section of his hut with the goats, called on him to face a new day...
Keywords: Juvenile Fiction / Adventure